Angngaru Tradition in Maros Regency Perspective ’ Urf - Nur, Muh.; Bakri, Muammar; Fatmawati, Fatmawati (International Journal of Islamic Studies, 2023)
This research focuses on the angngaru tradition in Maros Regency with an ’urf perspective with the aim of describing the angngaru tradition for the people of Maros Regency, then to find out the views of cultural figures, community leaders, religious leaders and angngaru practitioners for the people of Maros Regency and to find out the implementation of the angngaru tradition in the Regency Maros in ’urf perspective. The type of research used is field research with qualitative descriptive. Then two approach methods were used, namely the Sharia approach and then the historical approach. The results of the research show that after extracting information through direct interviews with sources, namely cultural figures, religious figures, community leaders, practitioners and the general public of Turikale Village, the author was able to draw the conclusion that the angngaru tradition in the Turikale community plays a big role in maintaining legal order. and the social order. This was proven after the author received information that those who carry out this tradition must meet several criteria, such as those who carry out the aru must be people who are selected and have been trained, must be humble and humble, and ready to participate in maintaining the goodness of the people being carried out. (the person who is doing the angngaru in front of him). The implementation of Islamic law towards this tradition can be done through the ’urf method approach, where the author concludes that this tradition has many benefits and does not violate Islamic values. So that the angngaru tradition in the ’urf perspective approach can continue to exist among the people of Maros Regency.